2002
DOI: 10.5713/ajas.2002.1110
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessments of Hormonal and Nutritional Treatments for Improvement of Awassi Sheep Production in Jordan

Abstract: The animal production sector in Jordan is characterized by shortages of locally produced feedstuffs derived from rangeland, forage plants or from human food crops as by products. This is exacerbated by insufficient rainfall, overgrazing, early grazing and high stocking rate. Thus, subject to these constraints, other technological improvements are highly desirable to meet the needs of crop growth and animal production. Alternative adapted technologies are also desirable in order to meet the increased demand for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Flugestone acetate is a synthetic analogue of progesterone and used for estrus synchronization of goats throughout the breeding and non-breeding periods. Additionally, intramuscular injection of a pregnant mare's serum gonadotropin (PMSG) at withdrawal of progestagen sponge is used for multi-ovulation (Nasr et al 2002, Whitley & Jackson, 2004. However, multi-ovulation causes multiple gestations and may increase the mortality rate of kids due to low birth weight or insufficient milk production by the mother for the consumption of each kid in equal amounts or insufficient maternal care.…”
Section: Introductionmentioning
confidence: 99%
“…Flugestone acetate is a synthetic analogue of progesterone and used for estrus synchronization of goats throughout the breeding and non-breeding periods. Additionally, intramuscular injection of a pregnant mare's serum gonadotropin (PMSG) at withdrawal of progestagen sponge is used for multi-ovulation (Nasr et al 2002, Whitley & Jackson, 2004. However, multi-ovulation causes multiple gestations and may increase the mortality rate of kids due to low birth weight or insufficient milk production by the mother for the consumption of each kid in equal amounts or insufficient maternal care.…”
Section: Introductionmentioning
confidence: 99%
“…In Greece, no specific financial assessment of the scheme has been made, although Gelasakis [ 14 ] considered the application of reproductive control as important for profit making in sheep and goat farming. A more precise assessment was made in Jordan by Nasr et al [ 15 ], who reported a profit of USD 8.36 per ewe in flocks in which reproductive control had been applied. Specific financial benefits in reproductive control were also reported by Yu et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%